2002
DOI: 10.1038/sj.ejcn.1601426
|View full text |Cite
|
Sign up to set email alerts
|

Selection of methodology to assess food intake

Abstract: Objective: The aim of the EFCOSUM project was to develop a method to estimate both acute and usual consumption levels in European countries and for the sake of comparison, a common basic method for dietary assessment was needed. The method should allow a reliable comparison of the intake of relevant dietary indicators among large population groups. Design and results: The selection of methodology was based on the available literature and the expertise of the participants. To guide the selection process, decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
373
0
17

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(391 citation statements)
references
References 39 publications
1
373
0
17
Order By: Relevance
“…Dietary intake data are notoriously difficult to obtain accurately. Twenty-four-hour recalls are relatively easy to perform, require low respondent commitment and allow the respondent to provide complete preparation and food type information (Biro et al, 2002). Although respondents may forget or omit information, the 24-h recall can be performed in any culture and it does not require the respondent to be literate or to record and alter his or her behavior in response to recording.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intake data are notoriously difficult to obtain accurately. Twenty-four-hour recalls are relatively easy to perform, require low respondent commitment and allow the respondent to provide complete preparation and food type information (Biro et al, 2002). Although respondents may forget or omit information, the 24-h recall can be performed in any culture and it does not require the respondent to be literate or to record and alter his or her behavior in response to recording.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was suggested that usual intake should be estimated by statistical modelling techniques using two non-consecutive 24-h recalls. 4 Following these recommendations and regarding the challenges to measure food consumption in adolescents, a computer-assisted self-administered tool, attractive for adolescents, was adapted for dietary assessment in the HELENA Study. 5 Energy and nutrient intake To calculate energy and nutrient intakes, food intake information has to be linked to food composition databases (FCDBs).…”
Section: Food Consumptionmentioning
confidence: 99%
“…Following the decision trees developed by EFCOSUM (Biró et al, 2002), the most pertinent choice made was that data will have to be collected on an individual level. The major reason for this choice is that, apart from general information on food availability, as is available via the DAFNE project, information is also needed at the individual level in order to know who is at risk from the nutritional point of view.…”
Section: Comparable Food Consumption Data In the Futurementioning
confidence: 99%